1997
DOI: 10.1038/37114
|View full text |Cite
|
Sign up to set email alerts
|

Antisaccade performance predicted by neuronal activity in the supplementary eye field

Abstract: The voluntary control of gaze implies the ability to make saccadic eye movements specified by abstract instructions, as well as the ability to repress unwanted orientating to sudden stimuli. Both of these abilities are challenged in the antisaccade task, because it requires subjects to look at an unmarked location opposite to a flashed stimulus, without glancing at it. Performance on this task depends on the frontal/prefrontal cortex and related structures, but the neuronal operations underlying antisaccades a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
216
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(240 citation statements)
references
References 26 publications
21
216
1
Order By: Relevance
“…Our results are consistent with the latter interpretation, as we found that, between puberty and adulthood, there is an increase in the prefrontal activity associated with the internal representation of the correct target location, which could direct or reinforce the appropriate movement. The prefrontal cortex is part of a broader network activated during the antisaccade task, and including the superior colliculus (45), basal ganglia (46), frontal eye fields (47), supplementary eye fields (48), and posterior parietal cortex (49). Our results do not preclude the possibility that developmental changes in neurophysiological activity occur in areas outside the prefrontal cortex, and that these may additionally affect motor or visualrelated activity related to the task.…”
Section: Discussionmentioning
confidence: 59%
“…Our results are consistent with the latter interpretation, as we found that, between puberty and adulthood, there is an increase in the prefrontal activity associated with the internal representation of the correct target location, which could direct or reinforce the appropriate movement. The prefrontal cortex is part of a broader network activated during the antisaccade task, and including the superior colliculus (45), basal ganglia (46), frontal eye fields (47), supplementary eye fields (48), and posterior parietal cortex (49). Our results do not preclude the possibility that developmental changes in neurophysiological activity occur in areas outside the prefrontal cortex, and that these may additionally affect motor or visualrelated activity related to the task.…”
Section: Discussionmentioning
confidence: 59%
“…FEF, SEF, DLPFC, posterior parietal cortex, anterior cingulate, striatum, and thalamus, more robustly than do prosaccades (Schlag-Rey et al, 1997;Guitton et al, 1985;Sweeney et al, 1996). Activation in the posterior parietal cortex was found within the IPS, in the precuneus, and in the SMG of the inferior parietal lobe.…”
Section: Brain Regions Subserving Antisaccadesmentioning
confidence: 91%
“…It has been used successfully to characterize development of the ability to voluntarily suppress prepotent responses throughout late childhood and adolescence (Fischer et al, 1997;Munoz et al, 1998). The brain systems subserving performance on the antisaccade task have been well-delineated in monkeys (Burman et al, 1997;Everling et al, 1999;Funahashi et al, 1993;Gottlieb et al, 1999;Schlag-Rey et al, 1997) and adult humans (Guitton et al, 1985;Sweeney et al, 1996;Muri et al, 1998;Doricchi et al, 1997;O'Driscoll et al, 1995). These areas include the frontal eye field (FEF), supplementary eye fields (SEF), dorsolateral prefrontal cortex (DLPFC), posterior parietal cortex, anterior cingulate cortex, basal ganglia, thalamus, and superior colliculus.…”
Section: Introductionmentioning
confidence: 99%
“…Gottlieb et al 1993;Gottlieb and Goldberg, 1999;Schlag-Rey et al 1997;Schlack et al 2003;Tian & Lynch, 1995). These are two frontal areas, the supplementary eye fields (SEF) and the frontal eye fields (FEF), and the posterior parietal cortex (PPC) (Berman et al 1999;Petit and Haxby 1999;O'Driscoll et al 1998).…”
Section: Discussionmentioning
confidence: 99%